2018
DOI: 10.1021/acs.accounts.7b00523
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cations on the Performance of Lithium Ion Batteries: A Quantitative Analytical Approach

Abstract: Lithium ion batteries are nowadays the state-of-the-art power sources for portable electronic devices and the most promising candidate for energy storage in large-size batteries, e.g., pure and hybrid vehicles. However, the degradation of the cell components minimizes both storage and operation lifetime (calendar and cycle life), which is called aging. Due to the numerous different aging effects, in either the single constituents or their interactions with each other, many reports about methodologies and techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 58 publications
0
39
0
Order By: Relevance
“…[29] Simple mixing of ac onventional organic carbonate solvent with al ithium bis(fluorosulfonyl)amide (LiFSI) salt at extremely high concentrations results in an unusual liquid with athreedimensional network of anions and solvent molecules strongly coordinating to Li + ions.W ang et al showed that this simple superconcentrated formulation inhibits the dissolution of both the aluminum and transition-metal cathodes (for this type of dissolution, see Ref. [30]) up to about 5V , and affords excellent cycling durability,ahigh rate capability, and enhanced safety of high-voltage LiNi 0.5 Mn 1.5 O 4 /graphite batteries because of its remarkable physicochemical properties,w hich are dependent on the optimum concentration of the considered salt in the electrolyte (Figure 2). [31] As ac onsequence in part to less friction between the anion and solvent molecules and the lower electrostatic interactions generated by the delocalized charge on the anion, lower viscosity may be achieved, as in the case of lithium 4,5-dicyano-2-(trifluoromethyl)imidazolide (LiTDI).…”
Section: Transport Properties:viscosity and Conductivitymentioning
confidence: 99%
“…[29] Simple mixing of ac onventional organic carbonate solvent with al ithium bis(fluorosulfonyl)amide (LiFSI) salt at extremely high concentrations results in an unusual liquid with athreedimensional network of anions and solvent molecules strongly coordinating to Li + ions.W ang et al showed that this simple superconcentrated formulation inhibits the dissolution of both the aluminum and transition-metal cathodes (for this type of dissolution, see Ref. [30]) up to about 5V , and affords excellent cycling durability,ahigh rate capability, and enhanced safety of high-voltage LiNi 0.5 Mn 1.5 O 4 /graphite batteries because of its remarkable physicochemical properties,w hich are dependent on the optimum concentration of the considered salt in the electrolyte (Figure 2). [31] As ac onsequence in part to less friction between the anion and solvent molecules and the lower electrostatic interactions generated by the delocalized charge on the anion, lower viscosity may be achieved, as in the case of lithium 4,5-dicyano-2-(trifluoromethyl)imidazolide (LiTDI).…”
Section: Transport Properties:viscosity and Conductivitymentioning
confidence: 99%
“…cathode-electrolyte interphase, CEI), which is comparable to the solid-electrolyte interface on the anode side but less known and investigated, occurs on the cathode surface. The electrolyte degradation also leads to transition metal reduction, in particular Ni 4+ for Ni-rich layered oxides, which are attributed to its low-lying lower upper molecular orbital (LUMO) [88][89][90].…”
Section: Electrolyte Degradation and Interphasial Reactionsmentioning
confidence: 99%
“…Note that the trapped Li on the graphite surface, conventionally known as "dead" Li, can originate from deposited metallic Li microstructures (e.g., dendrites) during long-term cycling and could pose severe safety concerns. [50][51][52][53][54] Interestingly, despite contributions from LiBOB decomposition, the Li content is much less in the LiBOB-tuned AEI with respect to the baseline sample after 500 cycles. In addition, much less electronically insulating LiF/MF x species are revealed at the graphite surface with LiBOB addition in the high-resolution F1s spectra ( Figure S11d, Supporting Information), suggesting greatly suppressed transition-metal dissolution from cathode.…”
Section: Anode Surface Chemistrymentioning
confidence: 99%